Screening method for Enzyme-based liquefaction of corn stover pellets at high solids. (November 2022) - Serra, Luana Assis; da Silva Cruz, Rosineide Gomes; Gutierrez, Diana M.R.; Cruz, Antonio José Gonçalves; Canizares, Carlos Alberto Torres; Chen, Xueli; Mosier, Nathan; Thompson, David; Aston, John; Dooley, James; Sharma, Pankaj; De Marco, Janice Lisboa; et al.
Graphical abstract: Highlights: Commercial enzyme preparations may be use to form 300 g/L slurries of corn stover. Pelleted corn stover, unlike free particulate form, gives high loadings. Some pellet lots (batches) are not readily liquefied. Laboratory assay distinguishes pellets with different liquefaction properties. Abstract: Liquefaction of high solid loadings of unpretreated corn stover pellets has been demonstrated with rheology of the resulting slurries enabling mixing and movement within biorefinery bioreactors. However, some forms of pelleted stover do not readily liquefy, so it is important to screen out lots of unsuitable pellets before processing is initiated. This work reports a laboratory assay that rapidly assesses whether pellets have the potential for enzyme-based liquefaction at high solids loadings. Twenty-eight pelleted corn stover (harvested at the same time and location) were analyzed using 20 mL enzyme solutions (3 FPU cellulase/ g biomass) at 30 % w/v solids loading. Imaging together with measurement of reducing sugars were performed over 24-hours. Some samples formed concentrated slurries of 300 mg/mL (dry basis) in the small-scale assay, which was later confirmed in an agitated bioreactor. Also, the laboratory assay showed potential for optimizing enzyme formulations that could be employed for slurry formation.